Favorable Gradients with the Mitroflow Aortic Valve Prosthesis in Everyday Surgery - Hartrumpf, Martin; Kuehnel, Ralf; Erb, Michael; Loladze, Giorgi; Mueller, Torsten; Albes, Johannes (The Thoracic and Cardiovascular Surgeon, 2012)
Background The supra-annular Mitroflow valve has been implanted for over 20 years, preferably in small aortic roots. Early outcomes and gradients in unselected elderly patients receiving aortic valve surgery are reported in this study.Methods Mitroflow valves were implanted in 190 consecutive patients (70% females). Mean age was 75.6 ± 5.5 years, body mass index was 28.2 ± 5.3 kg/m2, and logistic EuroSCORE 17.8 ± 16.5%. There were 170 single, 17 double, and 3 triple valve procedures. Of all, 46.8% of surgeries were performed with coronary artery bypass grafting and 39.5% were performed with isolated aortic valve replacement (AVR). Rates of redo and endocarditic cases were 14.2 and 4.7%.Results The 19-mm (n = 14), 21-mm (n = 135), and 23-mm (n = 41) valves showed mean gradients of 16.1 ± 7.4 mm Hg, 15.8 ± 7.1 mm Hg, and 11.6 ± 4.1 mm Hg, respectively, before discharge. Maximum gradients were 27.5 ± 13.0, 28.4 ± 12.6, and 21.6 ± 7.6 mm Hg, respectively. Correlation between gradients and sizes was significant. In-hospital mortality was 12.6% overall (6.7% in isolated AVR). The rate of valve-related events was low (mild paravalvular leakage 2.1%, neurologic 3.2%, bleeding 3.2%, atrioventricular block 4.2%, no thrombosis).Conclusion The Mitroflow valve can be safely implanted in elderly patients undergoing advanced surgical procedures. Gradients were acceptably low even in the smallest valves.
Keywords: aortic valve and root; heart valve surgery; outcomes (include mortality morbidity)